Squeeze film lubrication in piston rings and reciprocating contacts. (August 2015) - Taylor, RI
A detailed analysis of 'squeeze' lubrication effects in piston rings and reciprocating line contacts is reported. Inclusion of 'squeeze' effects leads to significant oil film thicknesses at reversal positions, and the pressure distribution in the lubricated contact can extend over the full face of the contact, whereas in models which neglect 'squeeze' effects, oil film thicknesses are predicted to be zero at reversal positions, and only half the contact is wetted. If it is desired to reduce friction losses without affecting durability, it is shown that one interesting 'co-engineering' option would be to use a lower viscosity lubricant, and at the same time, use 'flatter' piston rings. This is shown to lead to both lower friction and higher oil minimum film thicknesses. The model developed for piston rings can be applied to reciprocating line contacts with very little modification, and once again, it is found that the inclusion of 'squeeze' effects has a significant impact on oil film thickness, and it is also shown that the friction force is different dependent on the direction of sliding of the contact.